2013
DOI: 10.1017/sjp.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

Retiring from Elite Sports in Greece and Spain

Abstract: The main objective of the present study was to compare the athletic retirement of elite Greek and Spanish athletes in terms of (a) pre-conditions of retirement, (b) transitional period, and (c) consequences of the transition. For this purpose, elite athletes from Greece (n = 76) and Spain (n = 57) described in retrospect their experience leaving competitive sports through the Retirement from Sports Survey (Alfermann, Stambulova, & Zemaityte, 2004). Separate one-way ANOVAs and chi-square tests revealed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 33 publications
8
30
1
2
Order By: Relevance
“…Nevertheless, recent studies revealed that whilst a minority of retired Italian football players retired from the sport voluntarily and continued to be involved in football-related activities (D'Angelo et al, 2017), most Kenyan retired football players retire voluntarily and continue to be involved in football subsequently (in coaching, sports marketing or sports administration) (Rintaugu et al, 2016). Thus, previous studies have emphasised the need to understand how nationality and culture influence athletic termination (Dimoula, Torregrosa, Psychountaki, & Fernandez, 2013). For instance, the analysis of the loss of identity and the mental problems associated with the moment of termination or the analysis of the existence of a pre-termination plan or the psychological support required (Dimoula et al, 2013;Jones & Denison, 2017;Park et al, 2013;van Ramele, Aoki, Kerkhoffs, & Gouttebarge, 2017) in specific countries or the comparison between different countries and cultures should be considered in further studies.…”
Section: Athletic Terminationmentioning
confidence: 99%
“…Nevertheless, recent studies revealed that whilst a minority of retired Italian football players retired from the sport voluntarily and continued to be involved in football-related activities (D'Angelo et al, 2017), most Kenyan retired football players retire voluntarily and continue to be involved in football subsequently (in coaching, sports marketing or sports administration) (Rintaugu et al, 2016). Thus, previous studies have emphasised the need to understand how nationality and culture influence athletic termination (Dimoula, Torregrosa, Psychountaki, & Fernandez, 2013). For instance, the analysis of the loss of identity and the mental problems associated with the moment of termination or the analysis of the existence of a pre-termination plan or the psychological support required (Dimoula et al, 2013;Jones & Denison, 2017;Park et al, 2013;van Ramele, Aoki, Kerkhoffs, & Gouttebarge, 2017) in specific countries or the comparison between different countries and cultures should be considered in further studies.…”
Section: Athletic Terminationmentioning
confidence: 99%
“…Dimoula et al describe a cohort of 133 elite athletes in Greece and Spain who retrospectively detailed their experiences with leaving professional sports. From their study, the researchers concluded lack of retirement planning and high athletic identity after a sports career underlie difficulties with the retirement transition process (Dimoula, Torregrosa, Psychountaki, & Fernandez 2013). Other sports psychology researchers have proposed similar hypotheses for reduced quality of life in retired athletes (Werthner and Orlick 1986).…”
Section: Adjusting To Retirementmentioning
confidence: 99%
“…This is commonly known as athletic identity, or the degree to which one identifies as an athlete (Brewer et al 1993). It is important to take note of athletic identity for transitioning SAs because a strong athletic identity at the time of retirement is associated with adjustment difficulties (Erpič, Wylleman, & Zupančič 2004;Grove, Lavallee, & Gordon 1997;Martin, Fogarty, & Albion 2014), lack of post-collegiate planning (Dimoula, Torregrosa, Psychountaki 2013;Erpič et al 2004), and increased psychological difficulties (Erpič et al 2004;Grove et al 1997). These issues are consistent with the third-order factors of self-worth (coping self), realistic beliefs (coping self), and cultural identity (essential self).…”
mentioning
confidence: 99%